PERBEDAAN NILAI TOTAL LUNG CAPACITY, PEAK EXPIRATORY FLOW DAN EXPIRATORY RESERVE VOLUME ANTAR CABANG OLAHRAGA PADA ATLET USIA 6-12 TAHUN - Radyoko Heru Rahbanu; Yuswo Supatmo; Endang Kumaidah (Jurnal Kedokteran Diponegoro, 2016)
Background: The development of a person's lungs are the most rapidly while still a child. Activity plays an important role in lung development. Research shows that exercise a positive impact on the development of lung and cardiovascular function. Each type of sport has a different energy system depends on the type of training